Crosstalk of mRNA, miRNA, lncRNA, and circRNA and Their Regulatory Pattern in Pulmonary Fibrosis - Changye Li; Zhenkai Wang; Jinjin Zhang; Xueying Zhao; Pan Xu; Xiangyong Liu; Minge Li; Changjun Lv; Xiaodong Song (Elsevier, 2019)
Noncoding RNAs (ncRNAs), such as microRNA (miRNA), long ncRNA (lncRNA), and circular RNA (circRNA), are regulators of important biological functions. Therefore, understanding their crosstalk and regulatory patterns can provide treatment for diseases. In this study, differentially expressed RNA transcripts were obtained by RNA sequencing in bleomycin-induced pulmonary fibrosis in mice. Four miRNAs, 10 lncRNAs, and two circRNAs were tested to validate the sequencing. There were differentially expressed 585 mRNAs, 236 miRNAs, 272 lncRNAs, and 74 circRNAs in pulmonary fibrosis. Their location on chromosome, length varieties, interaction, and host genes were analyzed. lnc949, circ949, and circ057 were chosen to explore the detailed crosstalk and regulatory pattern, which were measured by using RNA-FISH, dual-luciferase reporter assay, real-time cell analysis and rescue experiment, co-localization analysis, RNA immunoprecipitation, and RNA pull down. The data showed that the three ncRNAs were predominant in the cytoplasm, and their regulatory patterns were focused on post-transcription. The fibrotic function of lnc949 depended on its host gene FKBP5. circ949 and circ057 formed a regulatory network with lnc865 and lnc556 to simultaneously regulate miR-29b-2-5p targeting STAT3 phosphorylation. Collectively, different RNAs can crosstalk with each other to regulate pulmonary fibrosis through different regulatory patterns. We hope these data can provide a full concept of RNA transcripts, leading to a new treatment for pulmonary fibrosis. Keywords: pulmonary fibrosis, mRNA, miRNA, lncRNA, circRNA